Feasibility of delivering and evaluating stratified care integrated with telehealth ('Rapid Stratified Telehealth') for patients with low back pain: protocol for a feasibility and pilot randomised controlled trial. Issue 1 (11th January 2022) - Zadro, Joshua R; Needs, Christopher; Foster, Nadine E; Martens, David; Coombs, Danielle M; Machado, Gustavo C; Adams, Cameron; Han, Christopher S; Maher, Christopher G
Abstract : Introduction: Long waiting time is an important barrier to accessing recommended care for low back pain (LBP) in Australia's public health system. This study describes the protocol for a randomised controlled trial (RCT) that aims to establish the feasibility of delivering and evaluating stratified care integrated with telehealth ('Rapid Stratified Telehealth'), which aims to reduce waiting times for LBP. Methods and analysis: We will conduct a single-centre feasibility and pilot RCT with nested qualitative interviews. Sixty participants with LBP newly referred to a hospital outpatient clinic will be randomised to receive Rapid Stratified Telehealth or usual care. Rapid Stratified Telehealth involves matching the mode and type of care to participants' risk of persistent disabling pain (using the Keele STarT MSK Tool) and presence of potential radiculopathy. 'Low risk' patients are matched to one session of advice over the telephone, 'medium risk' to telehealth physiotherapy plus App-based exercises, 'high risk' to telehealth physiotherapy, App-based exercises, and an online pain education programme, and 'potential radiculopathy' fast tracked to usual in-person care. Primary outcomes include the feasibility of delivering Rapid Stratified Telehealth (ie, acceptability assessed through interviews with clinicians and patients, intervention fidelity, appointment duration, App useability and online pain education programme usage) and evaluating Rapid Stratified Telehealth in a future trial (ie, recruitment rates, consent rates, lost to follow-up and missing data). Secondary outcomes include waiting times, number of appointments, intervention and healthcare costs, clinical outcomes (pain, function, quality of life, satisfaction), healthcare use and adverse events (AEs). Quantitative analyses will be descriptive and inform a future adequately-powered RCT. Interview data will be analysed using thematic analysis. Ethics and dissemination: This study has received approval from the Ethics Review Committee (RPAH Zone: X21-0221). Results will be published in peer-reviewed journals and presented at conferences. Trial registration number: ACTRN12621001104842.